New Neoribates (Acari, Oribatida, Parakalummidae) from Vietnam - Ermilov, Sergey G.; Starý, Josef (Zootaxa, 2017)
Three new species of oribatid mites of the genus Neoribates (Oribatida, Parakalummidae) are described based on adult specimens from the Tam Dao National Park of Northern Vietnam. Neoribates pseudojacoti sp. nov. differs from Neoribates jacoti Balogh & Mahunka, 1967 by the presence of clavate bothridial setae, median ridge of rostrum and adanal setae of medium size, and the localization of lamellar setae on prodorsum laterally to lamellar ends. Neoribates striatissimus sp. nov. differs from Neoribates similis Fujikawa, 2007 by the striate body surface, minute rostral setae and five pairs of genital setae. Neoribates protrusus sp. nov. differs from Neoribates rotundus Aoki, 1982 by the presence of barbed bothridial setae, rudimentary parts of translamellar line and very long interlamellar setae with attenuate tips.